ANALISIS PUISI NYANYIAN HAMZAH KARYA ABDUL HADI W.M (KAJIAN SEMIOTIK RIFFATERRE) - Husni Bt Salam (Cross-border, 2019)
This study aims to describe the indirectness of expression and to describe the meaning of heuristic and hermeneutic reading in Hamzaf Fanzuri's Nyanyian poem, by Abdul Hadi W.M. This type of research is descriptive research. The data in this study are the poetry of Hamzah Fanzuri's Nyanyian, by Abdul Hadi W.M, while the source of data in this study is a collection of poems by Abdul Hadi W.M. Matahari's Carrier, published in 2002 by PT Bentang Budaya. Data collection techniques used in this study were library techniques, reading techniques, and note-taking techniques. The data analysis technique in this study went through three stages, namely identifying all the building elements, classifying and then analyzing the data based on the indirectness of expression and giving meaning by reading heuristics and hermeneutics. From the results of data analysis, it can be concluded that heuristically, the poetry of Hamzah Fanzuri's Song, by Abdul Hadi W.M for meaning replacement, found one of seven figurative languages, namely the variety of figurative language, namely metaphor. For the deviation of meaning, two meaning substitutions were found, namely ambiguity and contradiction. In creating meaning, the elements that build on the poem are rhyme, homologues, and typography. Hermeneutically the poem Hamzah Fazuri's Song by Abdul Hadi W.M., means a poem that describes the poet's longing for God and the human relationship with God.